1996
DOI: 10.1074/jbc.271.28.16906
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Hamster Ovary Cells Expressing a Cell Surface-anchored Form of Hepatic Lipase

Abstract: The enzyme hepatic lipase may play several roles in lipoprotein metabolism. Recent investigation has suggested a role for the enzyme in lipoprotein and/or lipoprotein lipid uptake. To study this, a simple isolated system that mimics the in vivo system would be desirable. The enzyme is secreted by the hepatic parenchymal cell but exists, and presumably exerts its effects, while bound to capillary endothelial cells in the liver, adrenal gland, and the ovary. We constructed a cDNA that encodes the expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
32
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 66 publications
(31 reference statements)
5
32
1
Order By: Relevance
“…Both CHO cell lines were maintained in Ham's F-12 medium supplemented with 10% fetal bovine serum. These three cell lines were chosen because they are readily infected with recombinant adenoviral constructs and were successfully used in the past to characterize effects of LpL and HL on lipoprotein metabolism (16,37,44,45).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both CHO cell lines were maintained in Ham's F-12 medium supplemented with 10% fetal bovine serum. These three cell lines were chosen because they are readily infected with recombinant adenoviral constructs and were successfully used in the past to characterize effects of LpL and HL on lipoprotein metabolism (16,37,44,45).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, LpL had relatively small, if any, effects on HDL binding and holoparticle uptake, but significantly increased selective uptake of cholesterol esters from HDL particles (19 -22). Like LpL, HL has been shown to enhance binding and/or uptake of chylomicrons, chylomicron remnants, VLDL, and LDL by different cell types in vitro (15,16,23,24) via a HSPG-dependent process (15,16,23). In addition, in several studies HL efficiently increased holoparticle cellular uptake of HDL as well as selective uptake of cholesterol esters (16,25,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, HL could serve as a ligand that facilitates these interactions or, alternatively, could function as a coreceptor. In vitro studies have demonstrated that HL enhances the binding and/or uptake of chylomicrons, chylomicron remnants, ␤-very low density protein (VLDL), and LDL (15)(16)(17)(18)(19)(20) as well as HDL cholesterol (HDL-C) (18, 20 -22) in a variety of cell types. Cell-surface receptors, including the LDL receptor (LDLR), low density lipoprotein receptor-related protein (LRP), and SR-BI, as well as cellsurface proteoglycans, have been implicated in this process (15-17, 20, 22).…”
mentioning
confidence: 99%
“…In vitro studies have demonstrated that hepatic lipase enhances the binding or uptake of chylomicrons, chylomicron remnants, VLDL, LDL, [53][54][55][56][57][58] and HDL cholesterol (HDL-C) 56,59 -61 into a variety of cell types. Cell surface receptors, including the LDL receptor (LDLr), 55 LDLr-related protein (LRP), 53,60 and scavenger receptor B1 (SR-B1), 59,61 as well as cell surface proteoglycans, 54,60 have been implicated in these processes.…”
mentioning
confidence: 99%